Cyber crime: the global dimension - Grabosky, Peter (Henry Stewart Talks, 2008)
Theories of cyber crime, Illustrative cases of cross-border offending, Emerging trends, Jurisdiction and other legal issues, Successful investigations, Pluralistic responses
Archived at 2022/04/03